Effect of Adding Indigofera zollingeriana to Fermented Completed Feed from Pakchong (P. purpureum × P. americanum) at Different Harvest Ages on the Physical and Chemical Quality - Asyidiqy, Tantri; Karti, Panca Dewi Manu Hara; Abdullah, Luki (Jurnal Ilmu-Ilmu Peternakan, 2024)
This study aimed to evaluate fermented complete feed (FCF) based on various harvested ages of Pakchong (Pennisetum purpureum cv. Thailand) with the addition of Indigofera (Indigofera zollingeriana). This study used Pakchong at three different harvest ages, namely, 60, 70, and 80 days, which were then formulated by adding Indigofera at 10%, 20% and 30% of the total feed. A complete randomized design with a 3x4 factorial pattern was used, with the first factor being the age of the Pakchong grass and the second factor being the addition of Indigofera and 3 replications. The addition of different amounts of indigofera to complete fermented feed from pakchong grass at various harvest ages had a very significant effect (p<0.01) on the pH value, fleigh value (FV), crude protein (CP), neutral detergent fibre (NDF) and acid detergent fibre (ADF). The complete feed fermentation method has a vinegar aroma, crumb texture, color 2.5 Y 4/6, the best pH is 4.40, the highest FV is 90.76, the highest CP in this study is 13.88%, the NDF content is 55.91%, and the ADF content is 32.63%. The best harvest age was 80 days, and 30% indigofera